2002
DOI: 10.1046/j.1423-0410.2002.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased non‐transferrin bound iron in plasma‐depleted SAG‐M red blood cell units

Abstract: Increased levels of NTBI become detectable 17-22 days after donation and increase further with storage time. This excess NTBI may promote bacterial infection in iron-loaded individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
(25 reference statements)
0
14
0
Order By: Relevance
“…Several previous studies have shown that human stored blood also accumulates CFH and NTBI over time, producing levels of CFH from 80 to 90 mM (26) and NTBI from 5 to 15 mM. 33,34 Our study of canine stored blood showed that CFH and NTBI increased over the storage period, reaching mean levels of CFH of 190 mM and of NBTI of 8 mM at 6 weeks. The possibility exists that iron might increase the risk of transfusion by promoting bacterial growth, inducing inflammation, or both, as has been proposed previously.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Several previous studies have shown that human stored blood also accumulates CFH and NTBI over time, producing levels of CFH from 80 to 90 mM (26) and NTBI from 5 to 15 mM. 33,34 Our study of canine stored blood showed that CFH and NTBI increased over the storage period, reaching mean levels of CFH of 190 mM and of NBTI of 8 mM at 6 weeks. The possibility exists that iron might increase the risk of transfusion by promoting bacterial growth, inducing inflammation, or both, as has been proposed previously.…”
Section: Discussionmentioning
confidence: 51%
“…Our study demonstrates that washing removes 2 sources of iron: 1) iron in the form of NTBI as well as CFH, which accumulates over time in the storage bag, [32][33][34] and 2) older cells that are more likely to hemolyze in vivo after transfusion and release iron. Several previous studies have shown that human stored blood also accumulates CFH and NTBI over time, producing levels of CFH from 80 to 90 mM (26) and NTBI from 5 to 15 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Methaemoglobin levels, which normally constitute < 1% of total haemoglobin in the supernatant [8], are increased by twofold after 3 weeks of storage [56]. Free iron, which is essentially undetectable during the first few days of storage, is ubiquitous in the supernatant after 3 weeks of storage [35,57]. Similar to the post-transfusion effects of microvesicles (outlined above), the contents of the supernatant may also reduce endothelial-derived NO bioavailability and contribute to the oversaturation of the clearance systems for haemolysed red cells in the recipient.…”
Section: Reduced Red Cell Viabilitymentioning
confidence: 99%
“…Among the changes, most widely cited changes are [1 & ] a decrease in 2,3-diphosphoglycerate with age with associated increase in oxygen affinity limiting tissue oxygenation [2], an accumulation of potassium and lactic acid [3], an increase in adherence to vascular endothelial cells disrupting flow-perfusion [4], an early loss of nitric oxide bioactivity potentially leading to increased vasoreactivity, and [5] 20]. Finally, transfusion with older blood is not only associated with increased levels of CFH, but also transferrin bound iron (TBI), non-TBI, and plasma labile iron as iron is released from damaged RBCs [21]. Increased iron release has been shown to increase host inflammation and enhance bacterial growth, especially gram-negative species in in-vitro and in-vivo animal studies [ ], and Tung et al [33] demonstrated with lipopolysaccharide (LPS)-treated animals an increase in acute lung injury with older transfused blood that was not seen in animals without LPS-induced inflammation [34].…”
Section: Key Pointsmentioning
confidence: 99%